Intractable Headache in a Patient with Carcinoma Breast: Infiltrative or Infective - A Diagnostic Challenge - Maurya, Pradeep Kumar; Shukla, Saumya; Tiwari, Ashutosh; Shreshtha, Dinkar Kul; Singh, Ajai Kumar (Nepal Journal of Neuroscience, 2019)
Chronic meningitis is the inflammation of meanings having varied clinical manifestations and diverse etiologies. Among them tuberculosis continues to be an important cause of chronic meningitis. To achieve the etiological diagnosis, examination of cerebrospinal fluid is mandatory. Carcinomatous meningitis, another rare cause of chronic meningitis is caused by infiltration of leptomeninges by malignant cells. Diagnostics old standard of carcinomatous meningitis is to demonstrate malignant cells in the cerebrospinaluid. In cerebrospinal fluid negative cases with high degree of suspicion, various biomarkers may assist to arrive at diagnosis. However examination of single sample, delayed processing and low volume cerebrospinal fluid analysis may give rise to false negative results. Were port a patient of breast carcinoma presenting with intractable headache misdiagnosed as tuberculosis meningitis. Definitive diagnosis of carcinomatous meningitis was established by repeated lumbar puncture and large volume of cerebrospinal fluid was sent for immediate processing. Our case emphasizes the importance of the above parameters of cerebrospinal fluid study to maximize the diagnostic accuracy and efficiency.